Mitigation of progressive collapse of tall buildings - Tan, Kang Hai. (2011)
Since the impact of 911, various government bodies are increasingly concerned about a recurrence of the tragic event, brought about by terrorist actions. Thus, this topic of mitigation against progressive collapse of buildings is timely and crucial, particularly more even so, since the targets of terrorists’ activities have shifted from military hardened structures to soft civilian buildings. Chapter 1 of this report gives the background of the problem, setting the scene for the following works. Building fires usually take place after a blast event has occurred. It is well-acknowledged by structural engineers that the twin towers were brought down by ensuing intense fires instead of the initial impact and blast from the aeroplane. Thus, in view of this, the focus of the entire report is on the fire effects on structures, in particular, the connections and composite beams. The scope does not include blast effects on structures. Thus, chapter 1 introduces to readers compartment fire characteristics in Section 1.3 and ends with fire engineering design in Section 1.4. To mitigate against progressive collapse, performance-based approach should be used. In Chapter 2, the mathematical modelling of compartment fires is described through the concept of control volumes, one for the upper hotter layer and one for the lower cooler layer. Fire plume acts as a heat pump driving the convection of the fire dynamics. Pressure difference across the vent opening between the fire compartment interior and exterior drives the ambient air into the compartment through the lower layer and hot air out through the upper layer. The equations for different pressure gradients across the vent opening are described in Section 2.5. The numerical model CFMFAN is then compared with actual compartment fire test results in Section 2.8, followed by conclusions in Section 2.9. Chapter 3 presents the program FEMFAN3D which is a 3-D finite element program developed at NTU for the analysis of space skeletal steel frame. This forms the kernel of the work for this funded project. Following a brief review in literature in Section 3.2, the assumptions of the model are presented in Section 3.3. The derivations for displacement functions and the stress-strain relations are spelt out in the ensuing sections. Virtual work principle is used in the derivations (Section 3.6) of various terms in the stiffness matrix. The FEM code is followed by numerical validations in Section 3.12. A total of 5 case studies are considered, ranging from an academic problem of a sub-frame subjected to fire condition, space frame, semi-rigid connections to experimental validations. Chapter 4 presents the experimental work conducted in NTU through Dr Qian Zhenhai and Dr Ronny Budi Dharma. Dr Qian worked on the steel beam-to-column joint connections. A series of 6 cruciform specimens was tested to failure under elevated temperature conditions under restrained and unrestrained isothermal condition. The work on composite beams was conducted by Dr Ronny Budi Dharma. The ductility of such beams under fire conditions was addressed. Basically, although steel material softens under fire conditions, member ductility does not increase and in fact reduces with increasing temperature. This phenomenon is explained in this chapter. Due to space limitation, only the experimental works for connections and composite beams under fire conditions are presented. Details of their work can be found in their respective PhD thesis. The report ends with Chapter 5, which gives a broad-brush paint of practical design considerations for structural engineers when designing tall buildings against progressive collapse. In this chapter, both the blast and fire effects on connections are mentioned. There is also an attempt to address what is meant by progressive collapse from the design point of view. Two approaches to mitigate against progressive collapse are described in Section 5.4, viz. alternate load-path approach and indirect design approach. While one approach is more specific, the other provides a minimum level of protection towards structural resilience and robustness, particularly, with regard to the robustness of connections under catenary action. This has now become the new focus of study in a separate project funded by MHA and administered by DSTA. The chapter finishes with some updates on the recent experimental works related to progressive collapse of buildings.